Techno-functional properties and in vitro bile acid-binding capacities of tamarillo (Solanum betaceum Cav.) hydrocolloids - Gannasin, Sri Puvanesvari; Mohd Adzahan, Noranizan; Mustafa, Shuhaimi; Syed Muhammad, Sharifah Kharidah (Elsevier, 2016)
Hydrocolloids were extracted from seed mucilage and the pulp fractions from red tamarillo (Solanum betaceum Cav.) mesocarp, and characterisation of their techno-functional properties and in vitro bile acid-binding capacities was performed. The seed mucilage hydrocolloids that were extracted, using either 1% citric acid (THC) or water (THW), had a good foaming capacity (32–36%), whereas the pulp hydrocolloids that were extracted, using 72% ethanol (THE) or 20 mM HEPES buffer (THH), had no foaming capacity. The pulp hydrocolloid, however, possessed high oil-holding and water-holding capacities in the range of 3.3–3.6 g oil/g dry sample and 25–27 g water/g dry sample, respectively. This enabled the pulp hydrocolloid to entrap more bile acids (35–38% at a hydrocolloid concentration of 2%) in its gelatinous network in comparison to commercial oat fibre and other hydrocolloids studied. The exceptional emulsifying properties (80–96%) of both hydrocolloids suggest their potential applications as food emulsifiers and bile acid binders.